Pengaruh Faktor Sosial Ekonomi Terhadap Keputusan Penduduk Lanjut Usia untuk Bekerja (Studi Kasus Kota Semarang) - Ariq Hasna Salsabila; Herniwati Retno Handayani (Diponegoro Journal of Economics, 2020)
The increasing life expectancy in Semarang results in an increasing proportion of elderly population. The interesting matter to discuss regarding the increase of elderly population number is the elderly population depends on the productive-age population. In fact, many elderly population are able to keep working, 63.39 percent of elderly population in Semarang still work (BPS, 2017). The aim of this study is to analyze the socio-economic factors affecting the elderly population’s decision to work in Semarang. The independent variables in this study are education, family economic support, old age allowance, number of dependents, marital status,and health conditions. The study object is the elderly population who work and not work in Semarang with 100 samples. The types of data are primary and secondary data. The analysis method that used in this research is “Binary Logistic Regression”. The result shows that education, old age allowance, marital status, and health conditions have the negative and significant impact on the decision making of elderly either to work or not. In the other hand both family economic support, and the number of dependents are not significantly impact to decision making of elderly to work. The most dominant variable is education.